Mortality and Prognosis Factors of Elderly Patients with Pertrochanteric Fracture: Re-evaluationin Maharat Nakhon Ratchasima Hospital - Choovongkomol, MD, Kongtush; Lewsirirat, MD, Supphamard; Piyapromdee, MD, Urawit (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To study the one-year mortality rate and risk factors that affected one-year mortality of elderly pertrochanteric fracture patients. Methods: A retrospective cohort study of 682 pertrochanteric fracture patients, aged more than 60 years, treated at Maharat Nakhon Ratchasima hospital between January 2008 and December 2011 was carried out in which one-year mortality was assessed. The risk factors including treatment methods, gender, age, co[1]morbidities, American Society of Anesthesiologists classification, surgical methods, waiting time before surgery, and in-hospital complications were analyzed. Results: The overall one-year mortality rate was 29.33%. Factors that significantly affected one-year mortality were nonoperative treatment, age, more than one co-morbidity, chronic kidney disease, and in-hospital complications. The surgical group had a lower one-year mortality rate than the nonoperative group (odds ratio 0.21; 95% CI 0.15-0.3). Surgical methods and waiting time before surgery did not significantly affect mortality rates. In-hospital complications especially pneumonia and urinary tract infections significantly increased the one-year mortality rate (odds ratio 7.34; 95 % CI 3.18-13.95 and 1.23; 95 % CI 2.19-9.15, respectively) Conclusion: Elderly pertrochanteric fracture risk factors have to be considered to decrease one-year mortality. Operative treatment is the treatment of choice for elderly pertrochanteric fractures.